The Run up Tsunami Modeling in Bengkulu using the Spatial Interpolation of Kriging Technique - Yulian Fauzi; Suwarsono Suwarsono; Zulfia Memi Mayasari (Universitas Muhammadiyah Surakarta, 2014)
This research aims to design a tsunami hazard zone with the scenario of tsunami run-up height variation based on land use, slope and distance from the shoreline. The method used in this research is spatial modelling with GIS via Ordinary Kriging interpolation technique. Kriging interpolation method that is the best in this study is shown by Circular Kriging method with good semivariogram and RMSE values which are small compared to other RMSE kriging methods. The results shows that the area affected by the tsunami inundation run-up height, slope and land use. In the run-up to 30 meters, flooded areas are about 3,148.99 hectares or 20.7% of the total area of the city of Bengkulu.